1979
DOI: 10.1002/apmc.1979.050780115
|View full text |Cite
|
Sign up to set email alerts
|

Iodine reaction of vinyl acetate‐vinyl propionate copolymers, VI, thermochromism of the iodine complex membranes of poly(vinyl acetate) and vinyl acetate‐vinyl propionate copolymers

Abstract: The thermochromism of the iodine complex membranes of poly(viny1 acetate) and vinyl acetate-vinyl propionate copolymers was investigated at the states of different humidity. The complex membranes which were maintained in water and in wet air showed a reversible colour change by a heating-cooling cycle, while the complex membrane in dry air was irreversibly decoloured by heating. The decolouration of the complex membranes occurred quite sharply at a temperature characteristic of each membrane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1986
1986
2001
2001

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…4 The spectra of our iodine-PYA gels were very similar to those of the iodine-poly-( vinyl acetate) (PVAc) complexes reported by Hayashi et a/. 13 On the basis of Raman data, they concluded that the A.max due to 15 that of polycrystalline (benzamide hH + I 3 -used as the model substance. These considerations lead us to suppose that the shift of Amax from S20 nm to 620 nm, caused by increased D.H. and decreased temperature, may be attributed to the increase in the number of iodine atoms in a polyiodine chain.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…4 The spectra of our iodine-PYA gels were very similar to those of the iodine-poly-( vinyl acetate) (PVAc) complexes reported by Hayashi et a/. 13 On the basis of Raman data, they concluded that the A.max due to 15 that of polycrystalline (benzamide hH + I 3 -used as the model substance. These considerations lead us to suppose that the shift of Amax from S20 nm to 620 nm, caused by increased D.H. and decreased temperature, may be attributed to the increase in the number of iodine atoms in a polyiodine chain.…”
Section: Resultssupporting
confidence: 54%
“…The sudden beginning of stress relaxation in Figure 8 indicates a discontinuous increase in the mobility of the network chains at the temperature, implying a kind of transition in PV A gels. It has been reported 15 that the iodine-PVAc complex suddenly disappears when the temperature is over the glass transition point of the polymer. In our case, the decrease of the amount of complex occurs gradually, suggesting that the transition at 20oc is not 'the Tg where the chain mobility changes from that of solid to that of liquid.…”
Section: Resultsmentioning
confidence: 99%